Research laboratories and training undergraduate students from the freshman level to produce international conference-level publications - Murray, Victor (2014)
We present the first results of the teaching methodology applied at the Universidad de Ingeniería y Tecnología (UTEC), Lima, Peru, to involve undergraduate engineering students in advanced research projects starting at the freshman year. Students at UTEC start taking mandatory engineering semester projects, similar to Capstone projects, starting on the first semester. Students with good performance and, more important, with a high will to keep learning extra topics, are invited to participate, to learn using a project based learning methodology, in the Research Laboratories led by experienced professors. The successful students start participating in advanced research projects as developers. In this manuscript, we present the case of two students who started learning hardware design, in their freshman year, and by the beginning of the third academic year, their work, which was part of a collaborative project among UTEC, the University of New Mexico and the U.S. Air Force Research Laboratories was presented as an oral presentation, among grad school-level papers, in an international conference in microelectronics. Those students have not taken the courses related to those topics yet, but they are learning how to develop advanced research and development projects. This methodology is being applied with all the students at UTEC and our expectation is that similar results will be reached in different engineering programs.